2011
DOI: 10.1073/pnas.1018308108
|View full text |Cite
|
Sign up to set email alerts
|

Splitting of H3–H4 tetramers at transcriptionally active genes undergoing dynamic histone exchange

Abstract: Nucleosome deposition occurs on newly synthesized DNA during DNA replication and on transcriptionally active genes via nucleosome-remodeling complexes recruited by activator proteins and elongating RNA polymerase II. It has been long believed that histone deposition involves stable H3-H4 tetramers, such that newly deposited nucleosomes do not contain H3 and H4 molecules with their associated histone modifications from preexisting nucleosomes. However, biochemical analyses and recent experiments in mammalian ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 41 publications
8
61
1
Order By: Relevance
“…Tracking ''old'' and ''new'' histones had also demonstrated splitting of nucleosomes in yeast (Katan-Khaykovich and Struhl 2011) and in human cells (Huang et al 2013). Our results suggest that the half-nucleosome footprints at active loci in yeast are due to RSC action at these nucleosome positions, suggesting a possible mechanism for nucleosome splitting.…”
Section: Discussionmentioning
confidence: 66%
“…Tracking ''old'' and ''new'' histones had also demonstrated splitting of nucleosomes in yeast (Katan-Khaykovich and Struhl 2011) and in human cells (Huang et al 2013). Our results suggest that the half-nucleosome footprints at active loci in yeast are due to RSC action at these nucleosome positions, suggesting a possible mechanism for nucleosome splitting.…”
Section: Discussionmentioning
confidence: 66%
“…2). In yeast, where the single H3 isoform is homologous to H3.3, (H3-H4) 2 tetramer splitting can be observed on transcriptionally active loci (Katan-Khaykovich and Struhl, 2011). The same is observed in mammalian cells, although the frequency of (H3.3-H4) 2 splitting appears to correlate more with enhancer specificity and potentially during DNA replication (Huang et al, 2013;Xu et al, 2010).…”
Section: Histone Variants and Tetramer Splittingmentioning
confidence: 64%
“…A genomic-scale study in yeast (23) detected widespread subnucleosomal structures in dynamic chromatin, including what appear to be half-nucleosomes (consisting of one copy of each histone), hexasomes, and tetrasomes. Moreover, it was shown that in actively transcribing genes and their enhancers (which are also the sites of very active histone exchange), preexisting (H3$H4) 2 tetramers might split into dimers, resulting in mixed nucleosomes composed of old and new histones (86,87). The enhanced presence of mixed tetramers at sites of active transcription suggests that nucleosome perturbation by Pol II involves a transfer of parental H3$H4 as dimers.…”
Section: Interpretation Of Genome-wide Mapping Datamentioning
confidence: 99%